Impact of Telemedicine in Managing Chronic Conditions Within Family Medicine Practices in Abha City PHCs. - Al Saleh, Majed Mohammed; B Alamri , Faisal Suheam; Ali AlQahtani, Abdulaziz Mari; Alrofydi , Abdullah Mohammed; Hassan Alasiri, Hassan Adel; A Alasmari, Bandar; Saeed, Abdullah (Journal of Neonatal Surgery, 2025)
Background:Telemedicine is a cornerstone of chronic disease management worldwide and has only intensified following the COVID-19 pandemic. In Saudi Arabia, the application of the national digital-health plan under Vision 2030 has given prominence to telehealth delivery in primary health care (PHC) settings. Nevertheless, patient experience and quality of communication in family medicine clinics in Abha City have not been studied. Objectives:To assess the overall patient experience with telemedicine for chronic condition management and identify the factors influencing satisfaction among adults attending PHCs in Abha City, Saudi Arabia. Methods:A cross-sectional survey was conducted among 400 adults diagnosed with chronic conditions who had used telemedicine services in the past year. Data were collected using an electronic questionnaire covering demographics, telemedicine exposure, communication satisfaction, perceived benefits, and difficulties. Descriptive statistics, t-tests, ANOVA), Pearson correlations, and multiple linear regression analyses were performed using Python. Ethical approval was obtained from the Asian Ethics Committee (Ref: F9-2-2025). Results:Participants reported high satisfaction with telemedicine (mean ± SD = 4.11 ± 0.87). Communication satisfaction showed a strong positive correlation with overall experience (r = 0.64, p < 0.001). The regression analysis identified communication quality (β = 0.54, p < 0.001) and perceived benefits (β = 0.07, p = 0.03) as significant positive predictors, whereas reported difficulties (β = −0.11, p = 0.011) and age ≥ 61 years (β = −0.57, p = 0.035) were negative predictors. Sex differences were not statistically significant (p = 0.51). Conclusion:Telemedicine yielded high satisfaction among patients with chronic conditions in the Abha PHCs. Communication quality was the strongest determinant of positive experiences. Strategies to enhance virtual communication skills, digital literacy, and user support are essential to optimize telehealth outcomes within Saudi Arabia’s Vision 2030 framework (1–3).